Antibody–Prodrug Conjugates with KSP Inhibitors and Legumain‐Mediated Metabolite Formation. Issue 35 (15th April 2019) - Lerchen, Hans‐Georg; Stelte‐Ludwig, Beatrix; Berndt, Sandra; Sommer, Anette; Dietz, Lisa; Rebstock, Anne‐Sophie; Johannes, Sarah; Marx, Leo; Jörißen, Hannah; Mahlert, Christoph; Greven, Simone
Abstract: Many antibody–drug conjugates (ADCs) have failed to achieve a sufficient therapeutic window in clinical studies either due to target‐mediated or off‐target toxicities. To achieve an additional safety level, a new class of antibody–prodrug conjugates (APDCs) directed against different targets in solid tumors is here described. The tumor‐associated lysosomal endopeptidase legumain with a unique cleavage sequence was utilized for APDC metabolism. Legumain‐activatable APDCs were as potent as their cathepsin B‐activatable analogues. The peptide sequence susceptible to legumain cleavage was optimized for further discrimination of the formation of active metabolites within tumor cells versus healthy tissues, leveraging different tissue‐specific legumain activities. Optimized APDCs with slow legumain‐mediated conversion reduced preclinically the levels of active metabolite in healthy organs while retaining high activity against different TWEAKR‐ and B7H3‐expressing tumors. Abstract : Preferential metabolism in tumor versus healthy tissues. To further increase tumor selectivity of payload delivery, a new class of antibody–prodrug conjugates (APDCs) has been developed. In addition to antibody degradation, the lysosomal cleavage of a short peptide ("the cap") mediated by the tumor‐associated protease legumain is a key step for release of the active metabolite.